Costimulatory and coinhibitory immune checkpoint receptors in head and neck cancer: unleashing immune responses through therapeutic combinations. Issue 1 (December 2016) - Davis, Ruth; Ferris, Robert; Schmitt, Nicole
Abstract Head and neck squamous cell carcinoma (HNSCC) represents a model of escape from anti-tumor immunity. The high frequency of p53 tumor suppressor loss in HNSCC leads to genomic instability and immune stimulation through the generation of neoantigens. However, the aggressive nature of HNSCC tumors and significant rates of resistance to conventional therapies highlights the ability of HNSCC to evade this immune response. Advances in understanding the role of co-stimulatory and immune checkpoint receptors in HNSCC-mediated immunosuppression lay the foundation for development of novel therapeutic approaches. This article provides an overview of these co-stimulatory and immune checkpoint pathways, as well as a review of preclinical and clinical evidence supporting the modulation of these pathways in HNSCC. Finally, the synergistic potential of combining these approaches is discussed, along with an update of current clinical trials evaluating combinations of immune-based therapies in HNSCC patients.